Structural Insights into the Assembly of the Type III Secretion Needle Complex - Marlovits, Thomas C. (2004)
Type III secretion systems (TTSSs) mediate translocation of virulence factors into host cells. We report the 17-angstrom resolution structures of a central component of Salmonella typhimurium TTSS, the needle complex, and its assembly precursor, the bacterial envelope–anchored base. Both the base and the fully assembled needle complex adopted multiple oligomeric states in vivo, and needle assembly was accompanied by recruitment of the protein PrgJ as a structural component of the base. Moreover, conformational changes during needle assembly created scaffolds for anchoring both PrgJ and the needle substructure and may provide the basis for substrate-specificity switching during type III secretion.